Simulation as a tool for production optimization, in the case of plastic pipe manufacturing - Loor Alcivar https://orcid.org/0000-0001-9735-6836, Byron José; Carriel Sevillano, Ronny Pedro; Olvera Moran, Betsy Mabel; Rodríguez Merchán, Sonia Melissa (EASI: Engineering and Applied Sciences in Industry, 2025)
Simulation is a method that allows creating a scenario like the real one to predict specific events. The objectives was determine how simulation has become an essential tool to optimize production and estimate its decisive contribution to industrial development. Methodology quantitative, descriptive study, use of indirect observation in a plastic pipe processing plant, grinding area, extrusion-injection. The results obtained expressed that, the application of the Arena software facilitated the development of the simulation of the production process, whose positive impact on the decision to increase the number of mills from 3 to 4, eliminated the existing bottleneck, increasing the installed capacity in the next five years in 22%. It was concluded that, the simulation has become an essential tool in manufacturing organizations, which must be integrated into all areas of the production process, to guarantee successful decision-making in terms of supply, design, development, manufacturing, marketing, and after-sales service.